Synthesis of C1- and C8a-epimers of (+)-castanospermine from D-glucose derived gamma,delta-epoxyazide: intramolecular 5-endo epoxide opening approach - Kalamkar, Navnath B.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2011)
A concise synthesis of two diastereomers of (+)-castanospermine namely 1- and 8a-epi-castanospermine 1b and 1c, respectively, is reported from D-glucose. The methodology involves stereoselective cross metathesis of D-glucose derived alkene 2 with 4-bromo-1-butene followed by azide displacement and m-CPBA oxidation to afford diastereomeric gamma,delta-epoxyazides 5a/5b. The Staudinger reaction of epoxyazide 5a followed by reaction with benzylchloroformate (CbzCl) unexpectedly furnished 1,3-oxazinan-2-one derivative 7 whose stereochemistry was establish by single crystal X-ray. This helps to assign the stereochemistry in the epoxidation reaction. The reduction of 5a/5b was then carried out by transfer hydrogenation to provide gamma,delta-epoxyamine that concomitantly undergoes intramolecular 5-endo-tet cyclization to afford hydroxypyrrolidine ring skeleton with sugar framework-a precursor to castanospermine analogues 1b/1c. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: alkaloids; Cross metathesis; D-Glucose; Epoxide; Oxazinanone; Polyhydroxy indolizidines